Effects of tyrosine kinase and phosphatase inhibitors on mitosis progression in synchronized tobacco BY-2 cells - Sheremet, Ya.A.; Yemets, A.I.; Azmi, A.; VissenBerg, K.; Verbelen, J.P.; Blume, Ya.B. (Цитология и генетика, 2012)
To test whether reversible tubulin phosphorylation plays any role in the process of plant mitosis the effects of inhibitors of tyrosine kinases, herbimycin A, genistein and tyrphostin AG 18, and of an inhibitor of tyrosine phosphatases, sodium orthovanadate, on microtubule organization and mitosis progression in a synchronized BY-2 culture has been investigated. It was found that treatment with inhibitors of tyrosine kinases of BY-2 cells at the G2/M transition did not lead to visible disturbances of mitotic microtubule structures, while it did reduce the frequency of their appearance. We assume that a decreased tyrosine phosphorylation level could alter the microtubule dynamic instability parameters during interphase/prophase transition. All types of tyrosine kinase inhibitors used caused a prophase delay: herbimycin A and genistein for 2 h, and tyrphostin AG18 for 1 h. Thereafter the peak of mitosis was displaced for 1 h by herbimycin A or genistein exposure, but after tyrphostin AG18 treatment the timing of the mitosis-peak was comparable to that in control cells. Enhancement of tyrosine phosphorylation induced by the tyrosine phosphatase inhibitor resulted in the opposite effect on BY-2 mitosis transition. Culture treatment with sodium orthovanadate during 1 h resulted in an accelerated start of the prophase and did not lead to the alteration in time of the mitotic index peak formation, as compared to control cells. We suppose that the reversible tyrosine phosphorylation can be involved in the regulation of interphase to M phase transition possibly through regulation of microtubule dynamics in plant cells. Для изучения участия обратимого фосфорилирования белков в прохождении митоза растительной клеткой исследовано влияние на этот процесс и организацию микротрубочек в синхронизированной культуре BY-2 ингибиторов тирозинкиназ – гербимицина А, генистеина и тирфостина AG18, а также ингибитора тирозинфосфатаз – ортованадата натрия. Обнаружено, что обработка клеток BY-2 ингибиторами тирозинкиназ при прохождении G2/M фазы не приводила к видимым нарушениям митотических структур микротрубочек, однако вызывала уменьшение их количества. Возможно, снижение уровня фосфорилирования белков микротрубочек по остаткам тирозина может нарушать динамические свойства микротрубочек при прохождении интерфазы/профазы. Все использованные ингибиторы тирозинкиназ приводили к задержке вступления клеток в профазу: гербимицин А и генистеин – на 2 ч, тирфостин AG18 – на 1 ч. После обработки гербимицином А или генистеином отмечали задержку в появлении пика митоза на 1 ч по сравнению с контролем, а после обработки тирфостином AG18 изменений не было. Обработка культуры клеток ингибитором тирозинфосфатаз ортованадатом натрия на протяжении 1 ч оказывала противоположное воздействие на прохождение митоза: вступление клеток в профазу ускорялось, но без изменений во времени формирования митотического пика по сравнению с контролем. Можно предположить, что фосфорилирование белков по остаткам тирозина является важным звеном в регуляции перехода клеток из интерфазы в М-фазу посредством регуляции динамических свойств микротрубочек в растительных клетках. Щоб дослідити участь зворотного фосфорилювання білків у проходженні мітозу рослиною клітини, вивчено вплив на цей процес і організацію мікротрубочок в синхронізованій культурі BY-2 інгібіторів тирозинкіназ – гербіміцину А, геністеїну та тирфостину AG18, а також інгібітора тирозинфосфатаз – ортованадату натрію. Виявлено, що обробка клітин BY-2 інгібіторами тирозинкіназ при проходженні G2/M не призводила до очевидних порушень мітотичних структур, проте викликала зменшення їхньої кількості. Можливо, що зниження рівня тирозинфосфорилювання білків мікротрубочок по залишках тирозину може порушувати динамічні властивості мікротрубочок впродовж інтерфази/профази. Всі використані нами інгібітори тирозинкіназ призводили до затримки входження клітин у профазу: гербіміцин А і геністеїн – на 2 год, тирфостин AG18 – на 1 год. Після обробки гербіміцином А або геністеїном виявлено затримку в прояві піку мітозу на 1 год у порівнянні з контролем, а після обробки тирфостином AG18 змін не було. Обробка культури клітин інгібітором тирозинфосфатаз, ортованадатом натрію впродовж 1 год призводила до протилежного впливу на проходження мітозу: вступ клітин в профазу прискорювався, проте без змін в часі формування мітотичного піку в порівнянні із контролем. Можна зробити припущення про те, що зворотне тирозинфосфорилювання білків по залишках тирозину є важливою ланкою в регуляції переходу із інтерфази в М-фазу за рахунок регуляції динамічних властивостей мікротрубочок в рослинних клітинах.